Association between laboratory markers and Covid-19 disease severity and outcome: a retrospective cohort study in Saudi Arabia - Alamoudi, Aliaa Amr; Eldakhakhny, Sahar; Banjar, Haneen; Ajabnoor, Ghada; Aljohani, Sama Badr; Basheer, Rasha Ramadan; Eldakhakhny, Basmah; Badawi, Mazen; Elsamanoudy, Ayman (Frontiers in Immunology, 2023)
In Saudi Arabia, limited studies have evaluated factors including epidemiologic, clinical, and laboratory findings that are associated with COVID-19 disease. The aim of this paper was to identify laboratory parameters used in King Abdulaziz University Hospital which show an association with disease severity and patient outcome in the form of mortality. Age, gender, medical history, and laboratory parameters were all retrospectively assessed concerning disease severity and disease outcome in a total of 111 COVID-19 patients at King Abdulaziz University Hospital between July 2020 and August 2020. Patients were categorized into mild disease if they did not require ward admission, moderate if they met the Ministry of Health criteria for isolation ward admission, and severe if they were admitted to the ICU. Age but not gender was associated with the disease severity X2 (4, N = 110) = 27.2, p <0.001. Of all laboratory parameters on admission, only the levels of Albumin appeared to be significantly associated X2 (2, N =70) = 6.6, p < 0.05 with disease severity. Age but not gender was also significantly associated with disease outcome X2 (2, N = 110) = 12.8, p < 0.01. Interestingly, RBC count also showed a significant relation with disease outcome X2 (2, N = 71) = 6.1, p < 0.05. This study provides more understanding of the laboratory characteristics in our part of the world to efficiently manage the disease.